Determination of Heavy Metals in Hoplobatrachus occipitalis (Crowned Bullfrogs) and Water from Some Reservoirs in Kadawa Irrigation Project Kano, Nigeria - T.S. Kuiwa; C.E. Mbah; D.S. Abolude; N Lawal; MA Aminu (Journal of Applied Sciences and Environmental Management)
This study was carried out to evaluate the concentrations of heavy metals (Cd, Cu, Mn, Pb, and Zn) in water and crowned bullfrog (Hoplobatrachus occipitalis) organs/parts (muscle, liver, leg, lung and trunk) from Kadawa irrigation project, Kano State, Nigeria. Atomic Absorption Spectroscopy was carried out using Atomic Absorption Spectrometer (AAS) Buck Scientific VGP-210 model (2008). The mean concentration of heavy metals in water samples were 0.11 mg/L, 0.18 mg/L, 0.26 mg/L, and 3.65 mg/L for Cu, Mn, Pb and Zn respectively. The sequence of metal accumulation in all the organs was Zn > Pb > Mn > Cu. The highest concentration of Zn (77.38 mg/kg), Pb (1.81 mg/kg) and Mn (0.68 mg/kg) were found in the lung while Cu (0.07 mg/kg) was deposited more in the liver. Cadmium was not detected in all the samples analysed. Zinc and lead were the most accumulated metals in all the organs/parts with the range of 77.38 mg/kg - 18.10 mg/kg and 1.81 mg/kg - 0.13 mg/kg respectively. The highest accumulation of metals was found in the lung and liver. The organ/parts accumulation pattern was: lung > liver > trunk > muscle > leg for Zn, Pb and Mn, while liver > lung > trunk > muscle > leg was for Cu. Lung and liver have the highest bioaccumulation of heavy metals while the leg and muscle bioaccumulated the least heavy metals. Hence the water, liver and lung of H. occipitallis are unsafe for consumption, and therefore posed a threat to public health. Farmers should be trained on proper usage of agrochemical.